If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g + 2g = 0 Combine like terms: 7g + 2g = 9g 9g = 0 Solving 9g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by '9'. g = 0 Simplifying g = 0
| 7x-8y=15 | | =5n^2+17n+6 | | 5+2n-3= | | 7x+2=4x+8 | | x^2-12+11=0 | | =2x^2+3x-2 | | 3x+12=-69-7x | | 3x+31=12x-77 | | 2n-3+5= | | 5x+30=7x+10 | | 186-6x=6x+19 | | 6x+5y=50 | | 10x-150=2x-14 | | 12(t-4)+6t=6(3t+2)-11 | | 3x+6=x+10 | | .2(x+2)-.4(x+2)=-.2x-.4 | | 28n^2+70n=0 | | 20k=-320 | | w+8=10 | | 87-2x=16x+19 | | 163-2x=43x+23 | | -3(4p+6)-2(2-14p)=3(9+5p) | | 6-8x=75-29x | | -78-10x=10+22 | | 10-10x=106-31x | | 6x+1=5x+13 | | V^2+9v+14=0 | | x(x-4)=1 | | 81v^3-4v=0 | | -1(x-11)=-2 | | (-3x+x)(7+-x)= | | 10x^3(x-4)-5x(x-4)= |